Years of life lost due to metastatic melanoma in 12 countries. (3rd March 2016) - Thiam, Aminata; Zhao, Zhongyun; Quinn, Casey; Barber, Beth
Abstract: Background: Regionally or distantly metastatic melanoma (stages IIIB/C and IV) place a high burden on society. To quantify this burden, this study estimated years of life lost (YLL) per patient for adults with metastatic melanoma in 12 countries in 2014. Methods: General population growth and life expectancy were estimated from the Organization for Economic Co-operation and Development data and life tables for each country. Incidence of melanoma and mortality rates for the disease were based on GLOBOCAN and US registry data. The prevalence of metastatic melanoma was calculated using mortality rates and survival data from patients with melanoma. YLL per patient was estimated by the difference between the disease-free life expectancy and the life expectancy with metastatic melanoma. Results: YLL per patient were as follows: Australia, men = 19.9 years, women = 22.7 years; Brazil, 16.3, 19.8; Canada, 19.4, 22.3; France, 18.8, 23.1; Germany, 18.3, 20.8; Italy, 19.3, 22.7; Mexico, 17.2, 19.0; the Netherlands, 18.5, 21.5; Spain, 19.2, 23.1; Sweden 19.4, 22.0; the UK, 18.7, 21.2; and the US, 17.9, 20.6. Conclusions: The burden of metastatic melanoma as measured by YLL is substantial in all 12 countries; although there is variation across countries and between men and women.